2003
DOI: 10.1073/pnas.1832864100
|View full text |Cite|
|
Sign up to set email alerts
|

Odor maps of aldehydes and esters revealed by functional MRI in the glomerular layer of the mouse olfactory bulb

Abstract: authors note that Fig. 1 a and c, the third and fourth panels of Fig. 3a, and the first panel of Fig. 3b were printed incorrectly due to a printer's error. The corrected figures and their legends appear below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
152
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 57 publications
13
152
2
1
Order By: Relevance
“…Imaging studies using various activity markers have shown that odor compounds evoke spatially organized, combinatorial patterns of neural activity in OBs (Mombaerts et al, 1996;Friedrich and Korsching, 1998;Johnson et al, 1998;Rubin and Katz, 1999;Belluscio and Katz, 2001;Xu et al, 2003; and ALs (Joerges et al, 1997;Carlsson et al, 2002;Hansson et al, 2003). In most of these cases, however, the cell types imaged were unknown, although in others (Zhao et al, 1998;Araneda et al, 2000;Ma and Shepherd, 2000;Gaillard et al, 2002;Wachowiak and Cohen, 2003) primary-afferent input was imaged.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies using various activity markers have shown that odor compounds evoke spatially organized, combinatorial patterns of neural activity in OBs (Mombaerts et al, 1996;Friedrich and Korsching, 1998;Johnson et al, 1998;Rubin and Katz, 1999;Belluscio and Katz, 2001;Xu et al, 2003; and ALs (Joerges et al, 1997;Carlsson et al, 2002;Hansson et al, 2003). In most of these cases, however, the cell types imaged were unknown, although in others (Zhao et al, 1998;Araneda et al, 2000;Ma and Shepherd, 2000;Gaillard et al, 2002;Wachowiak and Cohen, 2003) primary-afferent input was imaged.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of functional magnetic resonance imaging (fMRI) shows constant progress. Recently, fMRI odour maps (Xu et al, 2003, Schafer et al, 2006 have been recorded in the mouse and rat, opening the possibility of a totally non-invasive glomeruli mapping on the entire olfactory bulb. We have presented here a detection method designed for a 2D image, but clearly it would also be valid for a volume.…”
Section: Assessing the Significance Of Spatial Detailsmentioning
confidence: 99%
“…They have been studied in considerable detail (Shepherd et al, 2004). These studies include anatomical characteristics Powell, 1971, 1972;Mori and Yoshihara, 1995;Lodovichi et al, 2003), pioneering work and additional studies on regional electrical characteristics of mitral cells (Bischofberger and Jonas, 1997;Christie and Westbrook, 2003;Debarbieux et al, 2003), synaptic interactions with sensory neurons and local neurons of the olfactory bulb (Nicoll, 1971;Nowycky et al, 1981;Carlson et al, 2000;Urban and Sakmann, 2002), and properties of mitral cell responses to electrical and odorant stimulation (Freeman, 1974;Harrison and Scott, 1986;Hamilton and Kauer, 1989;Charpak et al, 2001;Margrie et al, 2001;Wachowiak and Cohen, 2001;Cang and Isaacson, 2003;Margrie and Schaefer, 2003;Xu et al, 2003). The results of these studies show that mitral cells are complex operational units.…”
Section: Introductionmentioning
confidence: 99%